2005
DOI: 10.1111/j.1365-2958.2005.04506.x
|View full text |Cite
|
Sign up to set email alerts
|

A magnesium‐dependent mreB null mutant: implications for the role of mreB in Bacillus subtilis

Abstract: SummaryMreB shares a common prokaryotic ancestor with actin and is present in almost all rod-shaped bacteria. MreB proteins have been implicated in a range of important cell processes, including cell morphogenesis, chromosome segregation and cell polarity. The mreB gene frequently lies at the beginning of a cluster of genes, immediately upstream of the conserved mreC and mreD genes. RNA analysis showed that in Bacillus subtilis mreB is co-transcribed with mreC and that these genes form part of an operon under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(120 citation statements)
references
References 47 publications
(56 reference statements)
8
107
0
Order By: Relevance
“…We found that Mg 2+ inhibited the lysis of the ΔasnB mutant, and it was also previously shown to prevent the lysis of Δ mreB mutants (Formstone and Errington, 2005). Furthermore, Mg 2+ inhibits cell lysis induced by diverse conditions in unrelated Gram‐negative microorganisms (Rayman and MacLeod, 1975; Leduc et al ., 1982; Gschwender and Hofschneider, 1969).…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…We found that Mg 2+ inhibited the lysis of the ΔasnB mutant, and it was also previously shown to prevent the lysis of Δ mreB mutants (Formstone and Errington, 2005). Furthermore, Mg 2+ inhibits cell lysis induced by diverse conditions in unrelated Gram‐negative microorganisms (Rayman and MacLeod, 1975; Leduc et al ., 1982; Gschwender and Hofschneider, 1969).…”
Section: Resultssupporting
confidence: 79%
“…Hypotheses put forward to explain this effect include the idea that Mg 2+ may somehow rigidify the cell wall, or that it may affect the activity of cell wall associated enzymes, or both (Formstone and Errington, 2005). We have tested the effect of Mg 2+ on the rigidity of the cell wall of wild‐type B. subtilis cells using AFM and have found no effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations